Exploring the Heterogeneity of Non-Syndromic Hearing Loss: A Comprehensive Review of Implicated Genes and the Role of Whole Exome Sequencing - Barrak, Mohammed M.; Bonyadi, Morteza; Hasan Jasim Hami; Mohammed D. Al Ali; Riam Yousfe Muttair; Rawa Abdulkareem Abd (University of Thi-Qar Journal of Science, 2023)
Background: Hereditary hearing loss (HHL) accounts for approximately 50-60% of all hearing loss (HL) cases, highlighting the significant role genetics play in this condition. HHL can be mostly classified into two main forms: syndromic and non-syndromic. Of these, non-syndromic hearing loss (NSHL) is the most prevalent, contributing to over 70% of HHL cases. The hearing process involves a complex interplay of various components inside the ear, working together to convert sound waves into comprehensible signals for the brain. Non-syndromic hearing loss (NSHL) is known for its extraordinary diversity and complexity, influenced by a vast array of genes, with more than 120 identified thus far. These genes can be categorized into distinct functional groups, encompassing cochlear ion homeostasis, hair bundle development and cell adhesion, synaptic transmission, transcriptional regulation, and mitochondrial function. The advent of next-generation sequencing (NGS) technologies has been instrumental in unraveling the genetic underpinnings of NSHL. Among NGS techniques, whole exome sequencing (WES) appeared as a revolutionary advancement, outperforming other approaches like targeted panel sequencing and whole-genome sequencing in terms of cost-effectiveness and efficiency. WES not only aids in deciphering the genetic basis of hearing loss but also offers the potential to revolutionize patient care and diagnosis. It paves the way for a new era for precision medicine in the realm of hearing loss, promising more accurate and tailored treatments for affected individuals. This transformative approach is poised to bring about substantial advancements in our understanding of hereditary hearing loss and its clinical management.